Efektivitas Program Pusat Layanan Kesejahteraan Sosial Anak Integratif - Alya Nur Amalina; Lukman Arif (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
This research aims to determine the Effectiveness of the Integrated Child Social Welfare Service Center Program in the Surakarta City Social Services. The research employs a qualitative descriptive research design with a program effectiveness theory approach that consists of four aspects: 1) Program Target Accuracy; 2) Program Socialization; 3) Program Objectives; 4) Program Monitoring. The research is analyzed using data analysis techniques that involve four components: data collection, data presentation, data condensation, and conclusion. The research results show that the Integrated Child Social Welfare Service Center in Surakarta City, as the implementing body, has carried out its tasks and functions effectively. However, it is found that the program's socialization aspect has not been fully achieved.